Behavioural Observation Of Human Stationary And Sustained Activities In Pedestrian Priority Streets Of Johor Bahru - Ghahramanpouri, Amir; Lamit , Hasanuddin; Sedaghatnia , Sepideh (Penerbit Universiti Sains Malaysia, 2012)
Streets are considered to be major public spaces in the urban fabric. A pedestrian street is a street in which the carriageway space has been prioritised for pedestrian use. In Malaysia, due to enhancements of the streetscape and the promotion of the qualities of urban spaces, "pedestrianisation" has been suggested as a solution to recover space for pedestrian and non-traffic activities. A review of the literature has revealed that when people engage in a variety of activities, the streets become livelier. However, few empirical studies have addressed stationary and sustained activities in pedestrian streets. This research focused on pedestrian activities in Meldrum Walk and Segget Walk in Johor Bahru. Through behavioural observation, data on pedestrians of diverse age groups and genders, along with different types of activities and postures, were analysed. This study recommended that policy makers initiate conscious attempts to create diverse environments to attract a varied group of people to reside near pedestrian streets or attract visitors to frequent these streets. In addition, policy makers need to focus on interest groups, including children, senior citizens and/or disabled people, to make it easier for these groups to participate in activities in pedestrian streets.